Kritik terhadap Penerapan Demokrasi dari Masa Reformasi hingga Era Digital di Indonesia - Suryosumunar, John Abraham Ziswan; Noorzeha, Fuad (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2023)
Democracy is often interpreted as a system of government based on the sovereignty of the people. Democracy is considered an ideal system to be implemented in various countries, including Indonesia. However, in reality, the implementation of democracy in Indonesia still results in various forms of discrimination, centralisation of power, and injustice. The researcher seeks to understand the dynamics of the application and understanding of democracy in Indonesia by using the hermeneutic method, through tracing the historical continuity that occurred. The study conducted resulted in the understanding that: (1) Democracy in Indonesia has experienced its ups and downs from the independence period to the reformation period with various forms of implementation. The reformation period became one of the gates as well as a bridge from the transfer of centralised power to civilian-held decentralisation. (2) The multi-party system is one of the results of the decentralisation of power during the reformation period. The implementation of the multi-party system encourages multi-dynasty politics, due to political personalisation and patronage culture within each party. (3) The development of digital social media encourages the manipulation of signs that are the result of reality reduction. A democratic image is built through digital social media as a representation of siding with the people by the elites. However, the democratic image built through digital social media is in line with the monopoly of the concept of democracy in favour of certain groups, which is then a driving factor in the occurrence of social polarisation in every political contestation.